The persistence of gender pay and employment gaps in European countries. - Afonso, António; Blanco-Arana, María del Carmen (Springer Nature, 2025)
We assess the factors that influence the gender pay gap and gender employment gap across an unbalanced panel of 31 European countries over the period 2000–2022, and estimate a system generalized method of moment model (GMM). We find that tertiary education reduces gender pay gap, and part-time and temporary contracts significantly increase this gap. Moreover, part-time reduces significantly gender employment gap, and both secondary and tertiary education as well. Additionally, for countries with GDP per capita below the sample mean, temporary work and part-time work significantly increases the gender pay gap. Nevertheless, for both group of countries (below and above GDP per capita sample mean), temporary work increases, whereas part-time work decreases the gender employment gap, highlighting the importance of being working or not. Finally, in higher income countries, education is the crucial determinant in reducing these gaps. Results are robust with fixed effects models.
https://openpolicyfinder.jisc.ac.uk/id/publication/8304
Keywords: Discriminación sexual en el trabajo; Salarios; Mujeres - Salarios; Gender pay gap; Gender employment gap; Education level; Type of contract; GMM